Answer:
3x + 6
Step-by-step explanation:
It's A because x + x + x = 3x and 2+2+2 = 6
Answer:
5f + 7
Step-by-step explanation:
8f-3f+2+5
8f-3f is 5f and 2 + 5 is 7
5f+7
Answer:
Step-by-step explanation:
Since, Here the smaller number = 2n - 1
Since, Numbers are consecutive.
Therefore, remaining numbers are 2n - 1 + 2 , 2n - 1 + 2 + 2
= 2n +1, 2n +3
Thus, the sum of these all numbers = 2n - 1 + 2n + 1 + 2n +3
= ( By equating the like terms)
Answer:
B.
Step-by-step explanation:
y = x^2 - x - 12
y = (x-4)×(x+3) that means x it either 4 or -3
y = x + 3
for x = 4 ➡ y = 3+4 ➡7
for x = -3 ➡ y = -3 + 3➡0
(the answer key is most probably faulty there's no way for y to be 0 in both scenarios)
Answer:
C
Step-by-step explanation:
For the first one, there is a ratio of change greater than one so that is exponential growth.
The second one has exponential decay but its x is negative making it actually exponential decay even if graphed.
The third one has positive growth over an interval of negative x, so in terms of x there is exponential decay.
The fourth one is neither and if graphed is just points as there is a specific solution set.
In conclusion, the third is exponential decay!
Hope this helps :)